The spectra of IceCube neutrino (SIN) candidate sources – II. Source characterization. Issue 2 (13th December 2021) - Padovani, P; Giommi, P; Falomo, R; Oikonomou, F; Petropoulou, M; Glauch, T; Resconi, E; Treves, A; Paiano, S
ABSTRACT: Eight years after the first detection of high-energy astrophysical neutrinos by IceCube, we are still almost clueless as regards to their origin, although the case for blazars being neutrino sources is getting stronger. After the first significant association at the $3\!-\!3.5\, σ$ level in time and space with IceCube neutrinos, i.e. the blazar TXS 0506+056 at z = 0.3365, some of us have in fact selected a unique sample of 47 blazars, out of which ∼16 could be associated with individual neutrino track events detected by IceCube. Building upon our recent spectroscopy work on these objects, here we characterize them to determine their real nature and check if they are different from the rest of the blazar population. For the first time we also present a systematic study of the frequency of masquerading BL Lacs, i.e. flat-spectrum radio quasars with their broad lines swamped by non-thermal jet emission, in a γ-ray- and IceCube-selected sample, finding a fraction >24 per cent and possibly as high as 80 per cent. In terms of their broad-band properties, our sources appear to be indistinguishable from the rest of the blazar population. We also discuss two theoretical scenarios for neutrino emission, one in which neutrinos are produced in interactions of protons with jet photons and one in which the target photons are from the broad-line region. Both scenarios can equally account for the neutrino–blazar correlation observed by some of us. Future observations with neutrino telescopes and X-ray satellites will test them out.